Boosting solid-state flexible supercapacitors by employing tailored hierarchical carbon electrodes and a high-voltage organic gel electrolyte. Issue 48 (3rd December 2018) - Liu, Wenhao; Wang, Kai; Li, Chen; Zhang, Xiong; Sun, Xianzhong; Han, Jianwei; Wu, Xing-Long; Li, Feng; Ma, Yanwei
Abstract : We developed a 3.5 V solid-state flexible supercapacitor prototype by employing tailored hierarchical carbon electrodes and an organic gel electrolyte. Abstract : Supercapacitors with high energy density and long cycle life without decay in the consecutive bending operation are urgently required for the next generation of wearable electronic devices. Here, we report a high-voltage flexible supercapacitor with enhanced energy density, which can be attributed to the tailored hierarchical carbon (HC) electrode materials and organic gel electrolyte. HC derived from MOF@graphene is synthesized via a facile and environmentally friendly process, where MOF derived porous carbon polyhedra are in situ anchored on the graphene surface to form a hierarchical nano-architecture. The HC shows a synergistic effect of porous nanocarbon and graphene, and possesses a large surface area (2837 m 2 g −1 ), desired meso-/micropore distribution and superior conductivity. A 3.5 V solid-state flexible supercapacitor is constructed by employing HC electrodes and EMIMBF4 /PVDF-HFP gel electrolyte, and it demonstrates a superior specific capacitance (201 F g −1 ) and good cycle life. The energy and power densities are significantly promoted (86 W h kg −1 at 438 W kg −1 and 61 W h kg −1 at 17 500 W kg −1 ). Meanwhile, the flexible supercapacitor shows excellent mechanical bending performance, exhibiting negligible capacitance decay under various bending states and repeated bending cycles, representing its promising potential for application in wearable electronics.